2009
DOI: 10.1158/1541-7786.mcr-08-0274
|View full text |Cite
|
Sign up to set email alerts
|

The Human Host Defense Peptide LL-37 Induces Apoptosis in a Calpain- and Apoptosis-Inducing Factor–Dependent Manner Involving Bax Activity

Abstract: LL-37 is a human cationic host defense peptide (antimicrobial peptide) belonging to the cathelicidin family of peptides. In this study, LL-37 was shown to kill Jurkat T leukemia cells via apoptosis. A loss of mitochondrial membrane potential, DNA fragmentation, and phosphatidylserine externalization were detected following LL-37 exposure, whereas apoptosis was independent of caspase family members. The specific apoptotic pathway induced by LL-37 was defined through the utilization of Jurkat cells modified to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 69 publications
9
57
0
2
Order By: Relevance
“…An earlier paper published by our laboratory analyzed the mechanism of apoptosis induced in Jurkat T leukemia cells exposed to LL-37. 33 We found that Jurkat cells were killed by higher concentrations of LL-37 (50 to 200 mg/mL), through a calpain-dependent and apoptosis inducing factor-dependent pathway requiring the Bcl-2 family member, BAX.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…An earlier paper published by our laboratory analyzed the mechanism of apoptosis induced in Jurkat T leukemia cells exposed to LL-37. 33 We found that Jurkat cells were killed by higher concentrations of LL-37 (50 to 200 mg/mL), through a calpain-dependent and apoptosis inducing factor-dependent pathway requiring the Bcl-2 family member, BAX.…”
Section: Discussionmentioning
confidence: 82%
“…This may be due to the activation of cell death pathways that are not reliant on grA or B, such as the calpain-dependent mechanism previously described. 33 In this earlier study, higher concentrations of LL-37 (100 mg/mL) were required to induce apoptosis in cell lines such as Jurkat. Activation of calpain and the release of apoptosis inducing factor from mitochondria were found to be critical in the demise of the cell.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Accordingly, it seemed appropriate to test both compounds for one of the known influences of LL-37 on cells, namely its cell toxicity (31)(32)(33)(34). As a starting point, we chose concentrations of GA and LL-37 of 2-50 µg/ml, similar to the range used by Koenig et al for GA stimulation of cytokine production by RAW264.7 and murine bone-marrow-derived dendritic cells (12).…”
Section: Ga and Ll-37-mediated Leukotoxicitymentioning
confidence: 99%
“…Notably, recombinant LL-37 treatment reportedly kills Jurkat T leukemia cells by activating apoptosis that is caspase-independent but calpain-and AIF-dependent as shown by BAX activation and translocation to mitochondria (Fig. 5) [2,88]. Although LL-37 targeted receptor in Jurkat cells has not yet been reported, it is known that FPRL1, a LL-37-targeted GPCR is expressed in T lymphocytes [89].…”
Section: Hematologic Malignancymentioning
confidence: 99%